The Costs of Legal Limbo for Refugees in Canada: A Preliminary Study - Coates, Tim; Hayward, Caitlin (Refuge: Canada’s Journal on Refugees, 2005)
This paper is designed to provide a preliminary understanding of the barriers facing refugees in legal limbo in Canada. In particular, it will focus on the economic implications, for both protected persons and Canadian society at large, of maintaining tens of thousands of individuals in this difficult situation for extended periods of time. The findings are preliminary, and designed to indicate future avenues of research, as well as potential roadblocks to research in this area. The paper also includes some of the results of a survey of Convention refugees and the refugee-supporting organizations, conducted by the Public Justice Resource Centre. The initial conclusions indicate that the costs of limbo are large enough to warrant serious reconsideration of this stage of Canada’s refugee determination policy. The rationale for this study was to help key decision makers see the futility and the unnecessary cost to the government of keeping refugees in limbo.